Synthesis of 1, 6-hexanediol from HMF over double-layered catalysts of Pd/SiO2 + Ir–ReOx/SiO2 in a fixed-bed reactor. Issue 7 (10th December 2015) - Xiao, Bin; Zheng, Mingyuan; Li, Xinsheng; Pang, Jifeng; Sun, Ruiyan; Wang, Hua; Pang, Xiaoli; Wang, Aiqin; Wang, Xiaodong; Zhang, Tao
Abstract : 1, 6-Hexanediol (1, 6-HDO) was effectively prepared from 5-hydroxymethylfurfural (HMF) over double-layered catalysts of Pd/SiO2 + Ir–ReO x /SiO2 in a fixed-bed reactor. Abstract : 1, 6-Hexanediol (1, 6-HDO) was effectively prepared from 5-hydroxymethylfurfural (HMF) over double-layered catalysts of Pd/SiO2 + Ir–ReO x /SiO2 in a fixed-bed reactor. Under optimal reaction conditions (373 K, 7.0 MPa H2, in solvent mixtures of 40% water and 60% tetrahydrofuran (THF)), 57.8% yield of 1, 6-HDO was obtained. The double-layered catalysts loaded in double-layered beds showed much superior performance compared to that of a single catalyst of Pd–Ir–ReO x /SiO2, even when the same amount of active components were used in the catalysts. The reaction solvent significantly affected product distributions, giving a volcano-shape plot for the 1, 6-HDO yield as a function of the ratio of water to THF. Brønsted acidic sites were generated on the catalyst in the presence of water which played determining roles in 1, 6-HDO formation. A high pressure of H2 contributed to 1, 6-HDO formation by depressing the over-hydrogenolysis of reaction intermediates and products to form hexane and hexanol. The reaction route was proposed for HMF conversion to 1, 6-HDO on the basis of conditional experiments.